Dairy Marketing in Kerala - Vijayan P.K (Sri C. Achutha Menon Government College, Thrissur, University of Calicut, 2025)
This research investigates dairy marketing in Kerala from the perspectives of dairy farmers, focusing on their socioeconomic profile, challenges faced, and the ensuing impacts on farm profitability. Using a descriptive research design, the study collected data from 384 dairy farmers across three leading milk-producing districts in Kerala. Respondents in the cooperative system were chosen using a multistage random sampling technique, while those in the non-cooperative system were chosen using snowball sampling. The study adopts a non-parametric and non-linear approach for data analysis. The research looks into several key aspects, including the factors influencing profitability and channel selection, the satisfaction levels of dairy farmers, and their intentions to continue dairy farming. The study also explores the challenges faced by dairy farmers, which are categorized into supply, economic, demand, marketing, technical, and social factors. According to the findings, farmers who sell their produce through the non-cooperative sector are more profitable, mostly because of the higher prices that are offered there. Furthermore, the study finds that demand-related and economic constraints have a major impact on profitability. Profitability is found to be inversely related with farm size. With supply and financial factors having no discernible effect on profitability, the analysis also emphasizes the significance of price, procurement, demand, and other services in influencing the choice of marketing channels. Furthermore, the study indicates that dairy farmers in Kerala perceive a positive future for the industry, contingent upon adequate support for services related to herd management, market conditions, breeding, feeding, and infrastructure. Among these factors, feeding, breeding, and infrastructure were found to be the most significant determinants influencing farmers' intention to continue in dairy farming. A look at satisfaction levels in different marketing channels shows that dairy farmers who have opted both cooperative and non-cooperative systems have higher satisfaction with services. This is especially true for procurement facilities, demand, financial help, pricing, and incentives. These elements play a big role in their decision to stay in dairy farming. The study suggests that both cooperative and non-cooperative dairy marketing channels need to focus on improving demand, pricing, supply, and procurement services. This will help increase farmer satisfaction and keep them in the industry. Such improvements are vital for boosting Kerala's milk production sector and supporting inclusive growth, making the state more independent in dairy production.
Keywords: Dairy farmers; Cooperatives; Non-cooperatives; Profitability; Farm size